The Influence of Human Resource Management on Healthcare Workers' Performance through Workload as a Mediating Variable in Hospitals: Literature Review - Dewi Sartika; I Putu Sudayasa; Ruslan; Nani Yuniar; Hilda Harun; Sartiah Yusran (Journal of Health Science and Pharmacy, 2025)
Background: Human resource management (HRM) plays an important role in improving the quality of healthcare services in hospitals, but its effectiveness is often influenced by the workload experienced by healthcare workers. High workloads can reduce performance through increased stress and fatigue, potentially acting as a mediating variable in the relationship between HRM practices and healthcare worker performance. Objective: This study aims to identify and analyze the influence of human resource management practices on the performance of healthcare workers, with workload as a mediating variable, based on empirical evidence. Method:  This study uses a Systematic Literature Review (SLR) approach based on PRISMA guidelines by examining scientific publications from Google Scholar, PubMed, Scopus, ScienceDirect, and ResearchGate. The selected articles are original research written in Indonesian or English, published between 2020 and 2025, and investigate the relationship between HR practices, workload, and healthcare worker performance in hospitals. Results: A review of ten studies shows that HR management practices such as recruitment, training, performance appraisal, compensation, and organizational support have a significant impact on healthcare workers' performance. Workload has been found to be an important factor that not only directly affects performance, but also mediates the relationship between HR management variables and job outcomes. International research reinforces these findings by showing that workload, burnout, work engagement, and other psychosocial factors can serve as mediating pathways between HR practices and healthcare worker performance, highlighting the complexity of the mechanisms that influence hospital service quality. Conclusion: HR management practices have been proven to affect the performance of healthcare workers, and workload plays a significant role as a mediator in this relationship. To optimize performance, hospitals need to strengthen HR policies that are integrated with workload management, psychosocial support, and strategies to improve the work environment in order to achieve sustainable healthcare worker performance.